2017
DOI: 10.3892/etm.2017.5125
|View full text |Cite
|
Sign up to set email alerts
|

Shuyu capsules relieve liver‑qi depression by regulating ERK‑CREB‑BDNF signal pathway in central nervous system of rat

Abstract: The purpose of this study was to investigate the possible therapeutic mechanism of Shuyu capsules in liver-qi depression. Liver-qi depression rats were prepared based on chronic unpredictable mild stress (CUMS) and delayed constraint. Rats were gavaged with Shuyu capsule, fluoxetine, Radix Bupleuri and Radix Paeoniae Alba to constrct rat models. Body weight test, sucrose preference test and open-field test were applied to test rat models. Western blot analysis and quantitative real-time PCR was applied to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…The results of this study also con rmed that these three evaluation methods can effectively evaluate the rat model of anger-out and anger-in, and BXD and SY can effectively correct abnormal anger tendency by changing the score of ABT, OFT and SPT. This is consistent with the results of relevant reports 64,65 .…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study also con rmed that these three evaluation methods can effectively evaluate the rat model of anger-out and anger-in, and BXD and SY can effectively correct abnormal anger tendency by changing the score of ABT, OFT and SPT. This is consistent with the results of relevant reports 64,65 .…”
Section: Discussionsupporting
confidence: 94%
“…Luo et al confirmed that activation of the cAMP/PKA‐CREB pathway can increase the secretion of BDNF in hippocampal neurons and ultimately promote the recovery of learning and memory impairment in rats under chronic unpredictable mild stress. Wang et al demonstrated that Shuyu capsules can increase the phosphorylation of CREB by activating the ERK‐CREB signal transduction pathway, thereby increasing the secretion of neurotrophic factors in the central nervous system of rats. At the same time, studies have revealed that LLLT can also promote the secretion of neurotrophic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that stimulation of the ERK‐cAMP response element‐binding (CREB) or protein kinase A (PKA)‐CREB pathway can promote the secretion of various neurotrophic factors. In contrast to the proinflammatory M1 macrophages, the M2 type is capable of secreting many types of neurotrophic factors . This finding implies that modulation of the polarization state of the macrophages in the SCI lesion can be used to promote nerve repair, which has become a focus of research into SCI recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF could promote cell differentiation and proliferation of neural stem cells, has nutrition effects on many types of neurons, Evidence-Based Complementary and Alternative Medicine has a greater impact on the plasticity of neurons and the synthesis of neurotransmitters, and is also related to learning and memory [35]. In addition, other studies have shown that BDNF plays an important role in the pathogenesis of severe depression [34,36,37]. BDNF is involved in the survival of neurons and the regeneration of dopamine, 5-HT, and cholinergic neurons in the central nervous system, and it is also a molecular marker of synaptic plasticity [38].…”
Section: Discussionmentioning
confidence: 99%